Exosomal lncRNAs as diagnostic and therapeutic targets in multiple myeloma - Yan, Hong; Jiang, Nan; Li, Xiaoying; Lin, Chenyang; Wang, Fang; Zhang, Juan; Chen, Lijuan; Li, Dan (Frontiers in Oncology, 2025)
Multiple Myeloma (MM) is the second most common malignancy of the hematopoietic system, accounting for approximately 10% of all hematological malignancies, and currently, there is no complete cure. Existing research indicates that exosomal long non-coding RNAs (lncRNAs) play a crucial regulatory role in the initiation and progression of tumors, involving various interactions such as lncRNA-miRNA, lncRNA-mRNA, and lncRNA-RNA binding proteins (RBP). Despite the significant clinical application potential of exosomal lncRNAs, research in this area still faces challenges due to their low abundance and technical limitations. To our knowledge, this review is the first to comprehensively integrate and elucidate the three mechanisms of action of exosomal lncRNAs in MM, and to propose potential therapeutic targets and clinical cases based on these mechanisms. We highlight the latest advancements in the potential of exosomal lncRNAs as biomarkers and therapeutic targets, offering not only a comprehensive analysis of the role of exosomal lncRNAs in MM but also new perspectives and methods for future clinical diagnosis and treatment of multiple myeloma.